2014
DOI: 10.5389/ksae.2014.56.3.047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Cover and Soil Amendments on the NPS load Reduction from Alpine Fields

Abstract: We investigated the effect of straw mat cover and soil amendments on the reduction of runoff, non-point source pollution load and yield of a Chinese cabbage from alpine fields. Two plots on sandy loam soil were prepared. Experimental treatments were control and rice straw mat cover (3,300 kg/ha)+Polyacrylamide (PAM) (5 kg/ha)+Gypsum (1 ton/ha) (SPG). A variety of Chinese cabbage was cultivated and runoff was monitored during a growing season in 2012. Monitoring was conducted to seven times. Runoff rate of SPG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Shin et al . (, ) and Won et al () reported that runoff reduction on sand and loamy sand fields by the SPG and similar surface cover treatments was between 29.4 and 81.2% and between 70.9 and 95.1%, respectively. The runoff reduction on sandy loam fields by the SPG and the SM treatments in the present study ranged from 22.0 to 90.9%, and from 37.5 to 68.1%, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Shin et al . (, ) and Won et al () reported that runoff reduction on sand and loamy sand fields by the SPG and similar surface cover treatments was between 29.4 and 81.2% and between 70.9 and 95.1%, respectively. The runoff reduction on sandy loam fields by the SPG and the SM treatments in the present study ranged from 22.0 to 90.9%, and from 37.5 to 68.1%, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Thus the differences in runoff quantity mainly contributed to the large reduction in pollutant loads, and proved that runoff control at source must be a key objective in the control of agricultural NPS pollution. Shin et al (2014) and Won et al (2014) reported that the NPS pollution reduction on sand and loamy sand fields by SPG and similar surface cover treatments was between 13.8 and 95.1% and between 28.5 and 79.8%, respectively. The load reduction on sandy loam fields by the SPG and SM treatments in the present study ranged from 27.6 to 95.0%, and from 38.7 to 96.7%, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As the pattern of pollutant load from upland fields via runoff is likely to be affected by soil, crop, topography, and seasonal distribution of rainfall (Prosdocimi et al, 2016), we considered studies that were conducted in South Korea to provide information that is more relevant to Korean agricultural environment and thus can support the MAFRA's program. Among various BMPs adoptable to steep-sloping uplands fields, we focused on SCV (Shin et al, 2011a(Shin et al, , 2011b(Shin et al, , 2012(Shin et al, , 2013(Shin et al, , 2016Won et al, 2011Won et al, , 2013Won et al, , 2014 (Table 1), VFS (Choi and Jang, 2014;Lee et al, 2015) (Table 2), and VRD (Kim et al, 2012;Kim and Kim, 2015) (Table 3) as these three BMPs have been relatively well studied. Though a few modeling studies were also available, we did not include these studies.…”
Section: Data Collectionmentioning
confidence: 99%